Nitric oxide reduction with ethanol on palladium surfaces: a molecular beam study - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S.; Counsell, Jonathan; Gilbert, Lee; Bowker, Michael (Journal of Physical Chemistry C, 2009)
Nitric oxide (NO) reduction with ethanol has been carried out with molecular beam instruments in order to understand the influence of ethanol blended gasoline on NO reduction. Maximum NO reduction and nitrogen production was observed between 500 and 600 K. Oxidation products, CO, CO(2), and H(2)O were also observed. Beam switching experiments have been performed between fuel-rich and fuel-lean compositions to demonstrate that the NO reduction can be managed under net oxidizing conditions on Pd surfaces. Nitrogen production only occurs transiently on the relatively clean Pd surface in the oxygen-rich condition due to slow build up and blockage of the reaction by surface oxygen atoms. This shows the need to maintain relatively oxygen free surfaces to manage NO reduction under net-oxidizing conditions by beam oscillation between fuel-rich and fuel-lean compositions.

Carbon dissolution and segregation in Pd(110) - Bowker, Michael; Counsell, Jonathan; El-Abiary, Kareem; Gilbert, Lee; Morgan, Chris; Nagarajan, Sankaranarayanan; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2010)
The bulk-surface diffusion of carbon in Pd(110) has been investigated using Molecular beams to examine the clean-off of carbon with gas-phase oxygen. The dominant product of the reaction above 600 K is CO CO, is only produced at much lower temperatures where the lifetime of adsorbed CO is significant. The segregation from the bulk Only Occurs at a measurable rate at >750 K, while loss of carbon into the bulk call occur at much lower temperatures. The reaction of carbon at high temperatures shows two regimes: (i) a non steady-state evolution of CO due to the clean-off of surface carbon already present on the surface, followed by (ii) a near steady-state reaction due to the continuous diffusion of carbon to the surface.